WEALTH BEFORE HEALTH: PATENTING IN THE TIMES OF PANDEMIC - Aashi Maheshwari; Neeti Amin (International Journal of Legal Developments & Allied Issues, 2020)
Even as the debate on patents in pharmaceutical industry and affordable access to medicines goes on, the Covid-19 pandemic has brought more questions on the subsistence of patent regime during the pandemic. The economic theory of patent protection provides that patents foster innovation by protecting the efforts and investments of the innovators and this theory is generally cited for conferring patents to life saving medicines and vaccines in pharmaceutical industry. In these unprecedented times, the possibility of patent rights coming in way of large-scale production of medical equipment and devices for the benefit of masses and affordable access of the same cannot be ignored. Pharmaceutical giants usually look to recovering their R&D costs by patenting their medicines and selling them at exceptionally high prices. This poses an important question with regard to the functioning of the patent regime during such times, when a drug to fight off the virus would be no less than an essential drug after taking into consideration the number of people affected worldwide. This shall discuss the patentability criteria for drugs, the effects and ill-effects of grant of patent for such drugs to the pharmaceutical companies and the steps taken by countries to alter their patent regime for an effective administration during the pandemic. The article concludes with views of the authors on feasibility of grant of patent and suggestions on functioning of patent regime during pandemic.